Komunikuoti kultūrą : institucijos, strategijos, auditorijos Communicating culture : institutions, strategies, audiences - Klimavičiūtė-Minkštimienė, Greta (Vytautas Magnus University, 2015)
The book "Communicating Culture: Institutions, Strategies, Audiences" is an outcome of the research project "The Development of Communicative Competence of Cultural Institutions in the Context of Knowledge and Creative Society" conducted between 2012 and 2015 by researchers of Vytautas Magnus University. The data were collected from cultural organisations, project participants, in Kaunas, Šiauliai and Klaipėda between 2008 and 2013. The project had encompassed theoretical studies and their critical development, case studies and qualitative and qualitative data analysis. Central in the project was estimating to what extent the organisations were perceptive to the influences of creative and cultural industries (CCI) communication processes. The monograph aims to discuss processes, concepts, ideas and reasons why the above-mentioned traditional Lithuanian cultural institutions only partly implement CCI experiences and competences. A related goal is to consider how the efficacy of such institutions can be increased by adopting best practices pulled from CCI experiences in Lithuania and abroad and by implementing possibilities provided by new media. In the book, the essays revolve around the objective to show theoretical links between communicative action and CCI and to reveal their incongruities and points of tension. This is discussed in view of the data obtained within the framework of the above-mentioned research project. The data serve as a background for critical assessment of the dynamics of communicative competences in the researched cultural institutions over the past five years. The latter aspect is an integral part of the objective to discuss the relationship between communicative action, communicative reason and communicative space in regards to modern CCI developments. In this connection, the book also discusses contradictions arising in the formation of the creative class and examines how these contradictions stand in relation to organisational communication. Another objective of research presented in the book is to analyse and to compare communication among cultural institutions and structures related with these institutions. In particular, applied meanings and signs employed in communication are analysed from political and institutional perspectives. To this end, the study provides analysis and critical assessment of the specificity of communication in CCI organisations; probes into its functions and forms; looks at the existing and the necessary competences from the communicative point of view; describes and polemicises whether virtual space and new media are effectively used in communicative practices of cultural institutions.